Pillar[5]arene‐Stabilized Silver Nanoclusters: Extraordinary Stability and Luminescence Enhancement Induced by Host–Guest Interactions. (18th September 2019) - Muhammed, Madathumpady Abubaker Habeeb; Cruz, Laila Khalil; Emwas, Abdul‐Hamid; El‐Zohry, Ahmed M.; Moosa, Basem; Mohammed, Omar F.; Khashab, Niveen M.
Abstract: Herein, we report the synthesis of a new class of functional silver nanoclusters (AgNCs) capped with pillar[5]arene (P5)‐based host ligands. These NCs are readily prepared through direct synthesis or ligand exchange synthesis and are stable at room temperature for over 4 months. The pillar[5]arene‐stabilized NCs (Ag29 (LA‐P5)12 (TPP)2 ) endorse reversible host–guest interactions with neutral alkylamines and cationic quaternary ammonium guests. This results in the formation of spherical assemblies with unparalleled changes in their optical properties including an astonishing circa 2000‐fold luminescence enhancement. This is the highest luminescence enhancement ratio reported so far for such atomically precise NCs. Our synthetic protocol paves the way for the preparation of a new generation of metal nanoclusters protected by macrocyclic ligands with molecular recognition and selectivity toward specific guests. Abstract : Der Gast macht das Licht an : Wirt‐Gast‐Wechselwirkungen von Pillar[5]aren(P5)‐modifizierten Silbernanoclustern (Ag29 (LA‐P5)12 (TPP)2 mit Alkylaminen und quartären Ammoniummolekülen führten zur Modulation der optischen Eigenschaften der Nanocluster, darunter auch zu einer außergewöhnlichen Verstärkung der Photolumineszenz um das ca. 2000‐Fache.